Building a National Pediatric Cancer Center and Network in Paraguay: Lessons for Addressing Challenges in a Low-income Country. Issue 5 (July 2015) - Samudio, Angélica; Figueredo, Diego; Lassaletta, Alvaro; Zelada, Ofelia; Peris, Aníbal; Bogado Yinde, Luis; Relyea, George; Pérez, Antonio; Madero, Luis; Ribeiro, Raul; Masera, Giuseppe; Caniza, Miguela A.
Abstract : In Paraguay, cancer is among the leading causes of death among children. We report challenges and solutions for building the country's first pediatric cancer center at the National University School of Medicine (PCC-SM) and describe the outcomes of the National Network for Pediatric Cancer. We found that children with acute lymphoblastic leukemia treated between 2008 and 2012 had higher 3-year survival rates and lower treatment abandonment rates than did children treated between 2000 and 2007 before the network was established. This improvement directly coincided with the increased treatment capacity of the PCC-SM. Herein, we describe the role of local, national, and international contributors in improving the health care at Paraguay's PCC-SM and discuss how expediting access to specialized cancer diagnosis and care and implementing a system for referral and follow-up visits can improve cancer outcomes in other low-resource countries.